La economía política de las crisis de deuda soberanas: el estado actual del debate en torno a los mecanismos de reestructuración (Tema Central) - Fernández Alonso, José (2018)
The goal of this research is to analyze the state of the contemporary debate on the mechanisms for sovereign debt restructuring. The article begins by unraveling the main guidelines supported by the proposals with the greatest political and economic impact since the opening of the debate, focusing specially on the developments reported in the following years. It also identifies the promoters of each one of them and the arguments that they put forward –and they still use today– regarding the problems that determine all the processes of sovereign debt restructuring. Finally, the work culminates with some closing considerations.